Pengaruh Pandemi COVID-19 bagi Masyarakat Kurau Barat Kabupaten Bangka Tengah - Asmar Asmar; Wahri Sunanda; Dwi Novitasari (Fakultas Teknik, Universitas Bangka Belitung, 2021)
The Covid-19 pandemic has affected and changed many forms of human life activities. The impact is also not felt on certain community groups, but also affects the community in the village area, such as the 203 heads of families who live in Kurau Barat village, Bangka Tengah district. Various information obtained from the community, including; perceptions of the dangers of Covid-19. risk of contracting Covid-19, Covid-19 news, access to health protocols and the economic impact on the people of West Kurau